2017
DOI: 10.1177/0748730417738611
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Mathematical Analyses Relating Circadian Period and Phase of Entrainment in Neurospora crassa

Abstract: Circadian rhythms are observed in most organisms on earth and known to play a major role in successful adaptation to the 24 h cycling environment. Circadian phenotypes are characterized by a free running period that is observed in constant conditions and an entrained phase that is observed in cyclic conditions. Thus, the relationship between the free running period and phase of entrainment is of interest. A popular simple rule has been that the entrained phase is the expression of the period in a cycling envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…In other animal and human studies, an increased deviation of endogenous period length away from the environmental T cycle (e.g., 24-h LD cycle) or a decreased strength of the zeitgeber (e.g., light intensity) often result in marked increases in the phase angle (Pittendrigh and Daan, 1976;Jones et al, 1999;Dunlap et al, 2004;Gronfier et al, 2007). However, more recent genetic studies of the Neurospora clock question the assumed predictive/correlative relationship between period length and phase angle (Lee et al, 2017), and so the observation that Id2-/-mice express a normal period length but an altered phase angle is not a complete aberration. The phase angle difference in Id2-/-mice (smaller and delayed relative to WT mice under LD 12:12 conditions) is observed not only with wheel-running activity and by monitoring general activity within the cage but also in their profiles of feeding activity (Mathew et al, 2013), suggesting that this behavioral phase reflects the phase of the central pacemaker.…”
Section: Phase Angle Of Entrainmentmentioning
confidence: 99%
“…In other animal and human studies, an increased deviation of endogenous period length away from the environmental T cycle (e.g., 24-h LD cycle) or a decreased strength of the zeitgeber (e.g., light intensity) often result in marked increases in the phase angle (Pittendrigh and Daan, 1976;Jones et al, 1999;Dunlap et al, 2004;Gronfier et al, 2007). However, more recent genetic studies of the Neurospora clock question the assumed predictive/correlative relationship between period length and phase angle (Lee et al, 2017), and so the observation that Id2-/-mice express a normal period length but an altered phase angle is not a complete aberration. The phase angle difference in Id2-/-mice (smaller and delayed relative to WT mice under LD 12:12 conditions) is observed not only with wheel-running activity and by monitoring general activity within the cage but also in their profiles of feeding activity (Mathew et al, 2013), suggesting that this behavioral phase reflects the phase of the central pacemaker.…”
Section: Phase Angle Of Entrainmentmentioning
confidence: 99%
“…In turn, they show that this leads to faster reentrainment of the oscillators in a jet lag scenario. Lee et al [25] directly introduced a linear phase model to study the entrainment processes. They found that the period of the central and peripheral Whereas a shift of light phasing accompanied by a desynchronization is equivalent to changing both…”
Section: Related Workmentioning
confidence: 99%
“…In other animal and human studies, an increased deviation of endogenous period length away from the environmental T-cycle (24-h LD cycle) or a decreased strength of the zeitgeber (light intensity) often results in marked increases in the phase angle [5,22,31,32]. A popular simple rule is that a short period length produces an advanced phase relationship with the cycling environment, although there are exceptions to this predictive/correlative relationship [33]. In this study, we revealed that Id4−/− mice expressed a shorter freerunning period length.…”
Section: Discussionmentioning
confidence: 99%